Realist evaluation of cancer rehabilitation services in South Wales (REEACaRS): a mixed methods study protocol. Issue 4 (23rd April 2019) - Csontos, Judit Katalin; Fitzsimmons, Deborah; Jones, Mari; Wilkinson, Wendy M; Horton, Joanne; Love-Gould, Lisa; Tee, Anna; Watts, Tessa
Abstract : Introduction: Long-term and late effects of cancer treatments can cause functional limitations and reduce quality of life. Cancer rehabilitation services, which can comprise physical exercise, psychological support and educational interventions depending on the individual's needs, have been found to have a positive effect on health-related quality of life worldwide. However, accessibility or the lack of awareness on available help can act as barriers and influence the uptake of services, resulting in people having unmet rehabilitation needs. In Wales, UK, 41% of people, who have had health and social care needs resulting from cancer and its treatments, reported that they did not receive care when needed. The reason for this lack of support has not yet been fully investigated. The aim of this study is to investigate the conditions in which cancer rehabilitation services work and their underpinning mechanisms in South Wales, UK, specifically addressing barriers, facilitators and costs. Methods and analysis: Realist evaluation, which explains for whom a service works in what circumstances and how through context-mechanism-outcome pattern conjunctions, will be used in three phases to investigate the conditions in which cancer rehabilitation services work and their underpinning mechanisms. Phase 1 will be secondary analysis of a cancer rehabilitation database from a local Health Board to give context to who are accessing rehabilitation. Phase 2 will be thematic analysis of face-to-face, semistructured rehabilitation participant (n=20) and healthcare professional (n=20) interviews to explore the mechanisms of how cancer rehabilitation works. Phase 3 will be two case studies and cost-consequences analysis of cancer rehabilitation services. Ethics and dissemination: This study received favourable ethical opinion from London South-East Research Ethics Committee (17/LO/2123) in December 2017. This project is part of the author's PhD thesis and it is expected that the findings will be disseminated in academic journals and at local and international conferences.